1998
DOI: 10.1136/hrt.80.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heparin as an adjunct to thrombolysis for acute myocardial infarction: the FATIMA study

Abstract: Objective-To investigate the feasibility of fixed dose, weight adjusted subcutaneous low molecular weight heparin (LMWH), with monitoring of anti-Xa levels and assessment of coronary patency rates after three to five days, thereby giving an initial indication of its safety and eYcacy. Design-In 30 patients with acute myocardial infarction, LMWH (nadroparine) was given as a body weight adjusted intravenous bolus with thrombolysis (rt-PA infusion) and in weight adjusted subcutaneous doses at six hours, and every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…LMWH does not have much interference in inhibiting thrombin and fibrin formation on compared with other thrombolytic agents A study reported that on concomitant administration of heparin at its therapeutic dose with other thrombolytic agent -Tissue-type plasminogen activator (t-PA), heparin did not inhibit thrombolysis as compared with only t-PA treated blood samples (Fry and Sobel, 1988). But another study reported that LMWH on subcutaneous administration, it is effective and safety on usage as adjunct to rt-PA thrombolytic treatment for acute infarction (Chamuleau SA et al, 1998). From the present study, we inferred that normal saline has also some extent of inhibition against thrombin and fibrin formation.…”
Section: Resultsmentioning
confidence: 49%
“…LMWH does not have much interference in inhibiting thrombin and fibrin formation on compared with other thrombolytic agents A study reported that on concomitant administration of heparin at its therapeutic dose with other thrombolytic agent -Tissue-type plasminogen activator (t-PA), heparin did not inhibit thrombolysis as compared with only t-PA treated blood samples (Fry and Sobel, 1988). But another study reported that LMWH on subcutaneous administration, it is effective and safety on usage as adjunct to rt-PA thrombolytic treatment for acute infarction (Chamuleau SA et al, 1998). From the present study, we inferred that normal saline has also some extent of inhibition against thrombin and fibrin formation.…”
Section: Resultsmentioning
confidence: 49%